Experimental Study of RC Hollow Beams with Embedded PVC Pipes - Jen Hua Ling; Joseph Toh Sheng Ngu; Yong Tat Lim; Wen Kam Leong; How Teck Sia (Universitas Islam Sultan Agung, 2022)
This study investigated the behaviour of reinforced concrete (RC) hollow beams under incremental static loads. Polyvinyl Chloride (PVC) pipes were used to create longitudinal voids in hollow beams. The parameters studied included the size (25 mm, 50 mm and 75 mm diameter) and location (39 mm and 139 mm from beam soffit) of the PVC pipes in the beam. Nine specimens were tested under the four-point load test setup. The loads were progressively increased until the specimens failed. The specimens were analysed based on the failure modes, load-displacement responses and mechanical properties. The hollow beams gave a 2% to 36% lower strength than the solid beams. In terms of the strength per unit concrete, the hollow beams were less efficient than the solid beams. The efficiency ratio of hollow beams ranged from 0.67 to 1.0. For that, none of the proposed hollow beams was recommended.